Splendid coloration of the peacock spider Maratus splendens - Stavenga, Doekele G. (J R Soc Interface, 2016)
Jumping spiders are well known for their acute vision and often bright colours. The male peacock spider Maratus splendens is richly coloured by scales that cover the body. The colours of the white, cream and red scales, which have an elaborate shape with numerous spines, are pigmentary. Blue scales are unpigmented and have a structural colour, created by an intricate photonic system consisting of two chitinous layers with ridges, separated by an air gap, with on the inner sides of the chitin layers an array of filaments. We have characterized the optical properties of the scales by microspectrophotometry, imaging scatterometry and light and scanning electron microscopy. Optical modelling revealed that the filament array constitutes a novel structural coloration system, which subtly fine tunes the scale reflectance to the observed blue coloration.